SPEECH ACT ANALYSIS FOUND IN INSTAGRAM CAPTIONS OF "WHO INDONESIA” - Tira Nur Fitria (Kajian Linguistik dan Sastra, 2021)
Speech acts are utterances that contain action as a function of communication that considers aspects of the speech situation. The objective of this research is to analyze the type of speech act found in Instagram Captions of ‘WHO Indonesia”. This research uses descriptive qualitative research. There are 332 data which contains the speech act in Instagram Captions of ‘WHO Indonesia”. There are some types of speech acts found in Instagram captions in ‘WHO Indonesia”, they are directive, representative and expressive speech acts. 1) Directive speech act is a speech act that is performed so that the speaker does what the speaker says. In directive speech act shows 204 data or 61.45 % consist of positive forms, such as the use of base form or verb 1 and the use “let’s”, and the negative form such as the use verb “Don’t”. 2) Representative speech acts are speech acts that bind the speaker to the truth or fact. In representative speech act shows 120 data or 36.14 % which show opinion, assumption, stating, and informing. While Expressive speech acts are actions that are carried out to assess or evaluate what is mentioned in the speech. In an expressive speech, the act shows 8 data or 2.44 % which consists of the act of thanking, condolences, and congratulating.